J17 Apathy prevalence and clinical correlations in Huntington's disease. (29th August 2012) - Marques, I; Júlio, F; Januário, C
Abstract : Background: Neuropsychiatric symptoms are common in Huntington's disease (HD), often preceding motor symptoms onset. Apathy, believed to result from prefrontal-subcortical circuit dysfunction, is a frequent symptom with significant negative impact on patient's daily function. Aims: Estimate the prevalence and clinical correlates of apathy in a population of HD patients at different stages of disease severity. Methods: Evaluation of consecutive patients with genetically confirmed HD, followed at our department. Demographic, clinical and treatment data were collected. Marin's Apathy Evaluation Scale used for apathy assessment, Hamilton Depression Scale used for depression assessment and Montreal Cognitive Assessment (MOCA) used to evaluate cognitive impairment. Motor abnormalities quantified using UHDRS motor score. Statistical analysis with comparisons, correlations and regression analysis performed using SPSS software. p-values <0.05 considered statistically significant. Results: 30 patients included, 56.7% female, with mean age of 51.1±17.8 years and mean disease duration of 5.5±5.7 years. Number of CAG repeats varied from 38 to 49 (median: 43). Mean UHDRS motor score was 27.6±19.6. Apathy diagnosed in 40%, depression in 16.7% and cognitive impairment in 63.3% of patients. Patients with apathy had significantly higher UHDRS motor scores (p=0.001) and lower MOCA scores (p<0.001). Apathy Evaluation Scale score significantly correlated with UHDRS motor score (r=0.54, p=0.001) and MOCA score (r=−0.65, p<0.001). Linear regression analysis revealed significant inverse correlation between apathy and MOCA scores (β=−0.62, p=0.023). Conclusions: We identified a high prevalence of apathy in our patients and a strong correlation between apathy and cognitive dysfunction. Our results also suggest apathy and depression are independent entities with apathy being more prevalent in HD patients. Given the negative consequences of apathy, it must be considered an important target in HD treatment.